An Internet-Based Self-Help Intervention for Skin Picking (SaveMySkin): Pilot Randomized Controlled Trial - Gallinat, Christina; Moessner, Markus; Haenssle, Holger A; Winkler, Julia K; Backenstrass, Matthias; Bauer, Stephanie (JMIR Publications, 2019)
BackgroundIn spite of the psychosocial burden and medical risks associated with skin picking disorder, the health care system does not provide sufficient treatment for affected individuals to date. Therefore, an internet-based self-help program for skin picking was developed to offer easily accessible support for this population. ObjectiveThis pilot study evaluated the internet-based self-help program SaveMySkin. The 12-week program is based on cognitive-behavioral therapy and contains comprehensive information and exercises, a daily supportive monitoring system, and dermatological and psychological counseling via internet chat. Primary objectives were the investigation of attitudes and expectations toward the program, intervention effects on skin picking severity, user satisfaction, adherence, and willingness to participate. Secondary outcomes included the feasibility of study procedures, adequacy of assessment instruments, effects on skin picking-related impairment, dimensions of skin picking, and general psychological impairment. MethodsA two-arm randomized controlled trial was conducted in a sample of 133 participants (female: 124/133, 93.2%; mean age 26.67 [SD 6.42]) recruited via the internet. Inclusion required a minimum age of 17 years and at least mild skin picking severity. Participants were randomly allocated to the intervention (64/133, 48.1%) or waitlist control group (69/133, 51.9%). All assessments were conducted online and based on self-report. ResultsThe willingness to participate was very high in the study, so the initially planned sample size of 100 was exceeded after only 18 days. Participant expectations indicate that they believed the program to be beneficial for them (131/133, 98.5%) and provide a feeling of support (119/133, 89.5%). Reasons for study participation were insufficient outpatient health care (83/133, 62.4%) and flexibility regarding time (106/133, 79.7%) and location (109/133, 82.0%). The post-assessment was completed by 65.4% (87/133) of the sample. The majority of the intervention group who completed the entire post-assessment were satisfied with SaveMySkin (28/38, 74%) and agreed that the program is an appropriate support service (35/38, 92%). On average, participants viewed 29.31 (SD 42.02) pages in the program, and 47% (30/64) of the intervention group used the monitoring at least once a week. In comparison with the control group, the intervention group displayed substantial improvements in the skin picking severity total score (Cohen d=0.67) and especially on the subscale Symptom Severity (Cohen d=0.79). No effects on secondary outcomes were found. ConclusionsThis study confirms the need for easily accessible interventions for skin picking disorder and the high interest in internet-based self-help within the target population. It provides important insights into the attitudes toward online support and actual user experiences. Participant feedback will be used to further enhance the intervention. Our results point to the preliminary efficacy of SaveMySkin and may lay the foundation for future research into the efficacy and cost-effectiveness of the program in a multicenter clinical trial. Trial RegistrationGerman Clinical Trial Register DRKS00015236; https://www.drks.de/drks_web/navigate.do? navigationId=trial.HTML&TRIAL_ID=DRKS00015236 International Registered Report Identifier (IRRID)RR2-10.1016/j.conctc.2018.100315